The effect of coriander seed (Coriandrum sativum L.) as diet ingredient on the performance of Japanese quail - Güler, T; Ertas, ON; Çiftçi, M; Dalkiliç, B (South African Journal of Animal Sciences, 2005)
This study was conducted to determine the potential of coriander seed as a natural growth promoting substance in quail nutrition. Five hundred and ninety four 3-day old Japanese quails were divided into six groups of 99 birds each and randomly assigned to six treatment diets, Four of the diets contained coriander seed at 0.5%). 1% 2% or 4% levels of inclusion. one contained 10 mg of the antibiotic, avilamycin. per kg and a control group received no supplement. Effects on feed intake, daily live weight gain. feed conversion ratio and carcass characteristics of the birds were measured over a period of 42 days. After 42 days the highest feed intake was observed in the 4% coriander group, Birds receiving the diet containing 2% coriander seed showed the highest weight gain, followed by those receiving the diets containing 1% coriander seed. the antibiotic, the 4% and the 0.5% coriander seed, The control had the lowest weight gain. The feed conversion. ratio over the experimental period was significantly better in the group receiving 2% coriander seed than in the other treatments. The highest carcass yield and liver weights were also recorded in the 2% coriander group, while the lowest abdominal fat percentages were present in the 1%. 2% and 4% coriander groups, These results suggested that coriander seeds could be considered a. potential natural growth promoter for poultry. and showed the best responses at a 2% level of inclusion,
Keywords: coriander seed; antibiotics; performance; Japanese quail